Monitoring Pembangkit Listrik Tenaga Angin Menggunakan Arduino Berbasis GUI Matlab - Nila Gusriani; Muldi Yuhendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Wind power is a type of renewable energy power plant that is starting to develop in Indonesia. This plant uses wind turbines to convert wind power into mechanical power that will drive the generator. The generators used in this wind power plant have limited capabilities. In order to prevent operation that exceeds the capacity of the generator, it is necessary to monitor and protect the components of the wind power generator. This study proposes a wind power generator monitoring system using the Arduino MKR 1000 based on the Matlab Graphical User Interface (GUI). Wind power plant parameters that are monitored are wind speed, turbine rotation speed and generator output power. The tool made was tested on a wind power plant in the laboratory that uses a horizontal axis wind turbine with a permanent magnet type generator. The test results show that the wind power generator monitoring system made in this study has worked well. This can be seen from the wind speed data, the turbine rotation speed and the generator output power data displayed on the monitoring screen in accordance with the data available on the measuring instrument.